Teoretyczne i praktyczne wymiary procesu globalizacji. Analiza szans i zagrożeń - Rzepka, Agnieszka (My University, 2013)
Praca przedstawia jaki wpływ ma globalizacja na współczesne państwo, na teorie polityczne, na suwerenność, czy ogranicza myśl polityczną czy tylko modyfikuje ją. I czy państwa aby móc istnieć w skali globalnej muszą poddawać się globalizacji oraz czy występuje współzależność procesów globalizacji między kwestiami gospodarczo - ekonomicznymi a politycznymi. Celem racy jest analiza procesów globalizacji, jej szans oraz zagrożeń.

The study presents the influence that globalisation has on countries today, its influence on political theories and its influence on sovereignty. It also deals with the following questions: the question of whether it limits political thinking or merely modifies it; the question of whether countries have to give in to globalisation in order to exist on a global scale and the question of whether there is co- dependency of the processes of globalisation between issues related to the economy and economics and those related to politics. The aim of the study is to analyse the processes of globalisation, its oppportunities and threats.
Theorietical and the Practical Dimensions of the Process of Globalisation. An Analysis of Opportunities and Threats
Wydział Nauk Politycznych i Dziennikarstwa
Keywords: Globalizacja; Globalization; Polityka; Politics; Globalizm; Globalism; Globalność; Globality